Baghdad Markets in the Nineteenth Century, by the Pens of Some European Travelers (Journal of the College of Basic Education, 2022)
Since ancient times, Iraq attracted many tourists and early pioneers, due to its wide fame and reputation in the worlds of civilizations and antiquities, in addition to its abundant bounties and its distinguished geographical location, which was the subject of encouragement for most aspirants.During the last five centuries of our present era, the movement of dozens of delegations and missions of different nationalities and languages ​​flourished to Mesopotamia, to find out about its past and study its political, economic and cultural conditions, whether they were individuals or groups, and those centuries were full of that activity and vitality.However, the undeclared goals of those travelers in their coming to Iraq are limited in particular to providing their governments with information of political, economic and military importance, taking tourism, trade and exploration as a cover for it, and some of them originally came